A next step in adeno‐associated virus‐mediated gene therapy for neurological diseases: regulation and targeting. (23rd July 2013) - Chtarto, Abdelwahed; Bockstael, Olivier; Tshibangu, Terence; Dewitte, Olivier; Levivier, Marc; Tenenbaum, Liliane
Abstract : Recombinant adeno‐associated virus (rAAV) vectors mediating long term transgene expression are excellent gene therapy tools for chronic neurological diseases. While rAAV2 was the first serotype tested in the clinics, more efficient vectors derived from the rh10 serotype are currently being evaluated and other serotypes are likely to be tested in the near future. In addition, aside from the currently used stereotaxy‐guided intraparenchymal delivery, new techniques for global brain transduction (by intravenous or intra‐cerebrospinal injections) are very promising. Various strategies for therapeutic gene delivery to the central nervous system have been explored in human clinical trials in the past decade. Canavan disease, a genetic disease caused by an enzymatic deficiency, was the first to be approved. Three gene transfer paradigms for Parkinson's disease have been explored: converting L‐dopa into dopamine through AADC gene delivery in the putamen; synthesizing GABA through GAD gene delivery in the overactive subthalamic nucleus and providing neurotrophic support through neurturin gene delivery in the nigro‐striatal pathway. These pioneer clinical trials demonstrated the safety and tolerability of rAAV delivery in the human brain at moderate doses. Therapeutic effects however, were modest, emphasizing the need for higher doses of the therapeutic transgene product which could be achieved using more efficient vectors or expression cassettes. This will require re‐addressing pharmacological aspects, with attention to which cases require either localized and cell‐type specific expression or efficient brain‐wide transgene expression, and when it is necessary to modulate or terminate the administration of transgene product. The ongoing development of targeted and regulated rAAV vectors is described.